2004
DOI: 10.2337/diacare.27.7.1688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trandolapril and Its Fixed-Dose Combination With Verapamil on Proteinuria in Normotensive Adults With Type 2 Diabetes

Abstract: OBJECTIVE -To compare the effect of fixed-dose trandolapril-verapamil (FDTV) with that of trandolapril on proteinuria in normotensive, type 2 diabetic patients. RESEARCH DESIGN AND METHODS-A total of 60 normotensive, type 2 diabetic patients with 24-h proteinuria Ͼ300 mg were randomly assigned to two groups for open-label treatment. One group received 2 mg trandolapril/180 mg verapamil FDTV once daily; the other group received 2 mg trandolapril once daily. Study drugs were administered for 6 months in both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…In hypertensive patients with impaired glucose tolerance, the combination of trandolapril with verapamil reduced the risk of new-onset diabetes, as compared with an angiotensin receptor blocker plus a thiazide diuretic;105 in the Anglo-Scandinavian Cardiac Outcomes Trial-Blood Pressure Lowering Arm (ASCOT-BPLA),106 an ACE inhibitor/CCB combination lowered the risk of new-onset diabetes by 30%; in addition, type 2 diabetic patients treated with trandolapril plus verapamil had a better glycemic control than those treated with an ACE inhibitor as monotherapy, unrelated to their antihypertensive effect 107. The metabolic results are even better when new dihydropyridines are combined with ACE inhibitors.…”
Section: Ace Inhibitor Plus Ccbmentioning
confidence: 99%
“…In hypertensive patients with impaired glucose tolerance, the combination of trandolapril with verapamil reduced the risk of new-onset diabetes, as compared with an angiotensin receptor blocker plus a thiazide diuretic;105 in the Anglo-Scandinavian Cardiac Outcomes Trial-Blood Pressure Lowering Arm (ASCOT-BPLA),106 an ACE inhibitor/CCB combination lowered the risk of new-onset diabetes by 30%; in addition, type 2 diabetic patients treated with trandolapril plus verapamil had a better glycemic control than those treated with an ACE inhibitor as monotherapy, unrelated to their antihypertensive effect 107. The metabolic results are even better when new dihydropyridines are combined with ACE inhibitors.…”
Section: Ace Inhibitor Plus Ccbmentioning
confidence: 99%
“…However, we found that normotensive diabetes patients treated with the fixed-dose TV combination (for nephroprotection) reached a better fasting glycemic control than normotensive diabetes patients treated with monotherapy with trandolapril after 6 months of treatment. In that trial no patient received diuretics,31 leading us to hypothesize that the fixed-dose TV combination may have a role in glycemic control unrelated to its antihypertensive effect.…”
Section: Effects Beyond Their Antihypertensive Actionsmentioning
confidence: 99%
“…Of interest, the trandolapril/verapamil treatment decreased the incidence of microalbuminuria to a similar extent to trandolapril alone in type 2 hypertensive normoalbuminuric diabetic subjects 23 . Finally, in normotensive macroalbuminuric type 2 diabetic subjects, this combination did not alter the glomerular filtration rate, which was conversely significantly reduced in the trandolapril group 21 …”
Section: Combination Of An Acei or Arb And A Ccbmentioning
confidence: 75%
“…Specifically, the verapamil/trandolapril combination significantly reduced albuminuria to a greater extent when compared with atenolol/chlorthalidone 18 and to a similar degree in the enalapril/hydrochlorothiazide 20 treatment group. Furthermore, this specific combination, when compared with trandolapril 21,22 or verapamil 22 as monotherapies, had an additional effect in reducing proteinuria despite similar BP levels in both normotensive 21 and hypertensive 22 macroalbuminuric type 2 diabetic patients. Of interest, the trandolapril/verapamil treatment decreased the incidence of microalbuminuria to a similar extent to trandolapril alone in type 2 hypertensive normoalbuminuric diabetic subjects 23 .…”
Section: Combination Of An Acei or Arb And A Ccbmentioning
confidence: 93%